2011
DOI: 10.1007/s12020-011-9446-5
|View full text |Cite
|
Sign up to set email alerts
|

Insulin sensitivity, plasma adiponectin and sICAM-1 concentrations in patients with subclinical hypothyroidism: response to levothyroxine therapy

Abstract: Subclinical hypothyroidism is associated with an increased risk of atherosclerosis. The aim of this study was to investigate the concentration of plasma soluble intercellular adhesion molecule-1 and adiponectin in relation to insulin sensitivity in patients with subclinical hypothyroidism and to estimate if L-thyroxine treatment had an influence on these parameters. 13 women with subclinical hypothyroidism and 14 euthyroid controls were included in the study. A physical examination was conducted, hyperinsuline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 46 publications
4
20
0
Order By: Relevance
“…One explanation would be levothyroxine replacement causing a decrease in chronic inflammation, which plays an important role in HT. Previous studies showed decreased TNF-α, interleukin (IL)-1β, IL-6, and monocyte chemoattractant protein-1 levels in euthyroid group (24), decreased intercellular adhesion molecule-1 levels in subclinical hypothyroid group (25), and decreased C-reactive protein levels in another subclinical hypothyroid group after levothyroxine replacement (26). In addition, levothyroxine replacement has also been shown to decrease lymphocyte infiltration in rats and cats with HT (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…One explanation would be levothyroxine replacement causing a decrease in chronic inflammation, which plays an important role in HT. Previous studies showed decreased TNF-α, interleukin (IL)-1β, IL-6, and monocyte chemoattractant protein-1 levels in euthyroid group (24), decreased intercellular adhesion molecule-1 levels in subclinical hypothyroid group (25), and decreased C-reactive protein levels in another subclinical hypothyroid group after levothyroxine replacement (26). In addition, levothyroxine replacement has also been shown to decrease lymphocyte infiltration in rats and cats with HT (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies demonstrated that subclinical hypothyroidis leads to insulin resistance [31,32], but other studies did not observe this effect [33,34]. The reason for the differences in the obtained results may be due to different durations and degrees of subclinical hypothyroidism.…”
Section: Prace Oryginalnementioning
confidence: 94%
“…47, [67][68][69][70][71] Overall, it appears that the beneficial effect-if any-of levothyroxine treatment on lipid profile in SCH mainly concerns TC and LDL-C levels. TG concentrations are not significantly affected.…”
Section: Effect Of Levothyroxine Treatmentmentioning
confidence: 99%
“…As far as HDL-C is concerned, most studies demonstrate no significant effect of levothyroxine substitution on HDL-C concentrations in SCH. 16,18,20,24,47,[60][61][62][63][65][66][67]69,70 Nevertheless, there is limited evidence suggesting either a lowering 15,17,59,72 or an increasing effect.…”
Section: Effect Of Levothyroxine Treatmentmentioning
confidence: 99%